Morphological Spectrum of Endometrium in Patients with Abnormal Uterine Bleeding - Nazia Noor, Sidra Javed, Remisha Zahid Shah, Fariha Sahrish, Amema Hafeez, Mehwish Niazi (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Abnormal uterine bleeding (AUB) is one of the major problems requiring gynecological consultation. Biopsy proved to be gold standard for the accurate diagnosis of abnormal bleeding. It is more frequently observed in perimenopausal females. Aim: To determine morphological spectrum of endometrium in patients of pre and post-menopausal age groups with abnormal uterine bleeding. Study Design: Descriptive-cross-sectional study Place and duration of study: Department of Histopathology, K. E. Medical University Lahore from 31-07-2018 31-01-2019 Methodology: Three hundred and eighty four patients undergoing diagnostic dilatation and curettage or hysterectomy for abnormal uterine bleeding were included. Their demographic features i-e age and address were noted. The biopsies received in Pathology Department were formalin fixed, after tissue processing and cutting the slides were prepared and stained with haematoxylin and eosin stains. Results: There were 311(80.99%) patients between 25-50 years of age whereas 73(19.01%) between 51-60 years of age. Morphological spectrum of endometrium in patients of pre and post-menopausal age groups with abnormal uterine bleeding shows that 71(18.49%) had proliferative morphology, 58(15.10%) had secretary, 37(9.64%) had simple hyperplasia, 56(14.58%) had complex hyperplasia, 17(4.43%) had atrophic endometrium and 145(37.76%) had other type of morphology (may include mechanical causes such as intrauterine contraceptive device and malignancy). Conclusion: Morphological spectrum of endometrium in patients of pre and postmenopausal age groups with abnormal uterine bleeding shows proliferative morphology as the common morphology followed by secretary, simple hyperplasia, and complex hyperplasia.